2002
DOI: 10.1038/oby.2002.37
|View full text |Cite
|
Sign up to set email alerts
|

Work‐Related Physical Activity Is Not Associated with Body Mass Index and Obesity

Abstract: GUTIÉ RREZ-FISAC, JUAN L., PILAR GUALLAR-CASTILLÓ N, LUCÍA DÍEZ-GAÑ Á N, ESTHER LÓ PEZ GARCÍA, JOSE R. BANEGAS BANEGAS, AND FERNANDO RODRÍGUEZ ARTALEJO. Work-related physical activity is not associated with body mass index and obesity. Obes Res. 2002;10:270 -276. Objective: To analyze the association of work-related physical activity (WRPA) and leisure-time physical activity (LTPA) with body mass index (BMI) and obesity in the Spanish adult population aged 20 to 60 years. Research Methods and Procedures:The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
3
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 28 publications
7
60
3
2
Order By: Relevance
“…Then, a residual confounding effect on the relationship with BMI is possible. However, our results are in line with the findings of other population studies, 15,70 which found no association between work-related physical activity and BMI. The relationship between leisure-time physical activity and BMI has been found to be stronger in women than men.…”
Section: Discussionsupporting
confidence: 93%
“…Then, a residual confounding effect on the relationship with BMI is possible. However, our results are in line with the findings of other population studies, 15,70 which found no association between work-related physical activity and BMI. The relationship between leisure-time physical activity and BMI has been found to be stronger in women than men.…”
Section: Discussionsupporting
confidence: 93%
“…32 Gutiérrez-Fisac et al suggest that a socioeconomic interpretation may not be plausible, as most studies adjust for socioeconomic position. 30 Instead, the authors suggest that differences in diet and energy intake, factors that are less commonly measured or adjusted for in social epidemiological studies, may explain why greater levels of occupational activity do not appear to translate into lower BMI. 30 In addition, evidence from the MONICA study suggested that individuals with higher levels of occupational physical activity had a higher BMI and a greater risk of fatal myocardial infarction than inactive individuals, even after controlling for cardiovascular risk factors and socioeconomic position.…”
Section: Discussionmentioning
confidence: 99%
“…30 Instead, the authors suggest that differences in diet and energy intake, factors that are less commonly measured or adjusted for in social epidemiological studies, may explain why greater levels of occupational activity do not appear to translate into lower BMI. 30 In addition, evidence from the MONICA study suggested that individuals with higher levels of occupational physical activity had a higher BMI and a greater risk of fatal myocardial infarction than inactive individuals, even after controlling for cardiovascular risk factors and socioeconomic position. 33 The authors hypothesised that work related physical activity might have different effects on basal metabolic rate than other forms of physical activity, especially when combined with shift working.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that a positive energy balance (decreased energy expenditure by low level of physical activity and/or increased dietary energy intake by relative cheapness of processed foods, large portion sizes, immediate availability of fast foods, high-fat or high-energy diet and so on) is also a major reason for the increased prevalence of overweight Swiss from the 1980s until today; however, the phenomenon has been delayed by at least 30 years compared with the United States (Groscurth et al, 2003;Komlos et al, 2009;Statistisches Amt Basel Stadt, 2009). Although Henneberg and Veitch (2005) found that variance in BMI is strongly influenced by the components of the lean body mass (size of the musclo-skeletal system and the intra-abdominal contents) and not only by the amount of subcutaneous adipose tissue, genetic factors may also be another reason for this variance (James, 2001;Gutiérrez-Fisac et al, 2002;Katzmarzyk, 2002;Dina et al, 2007). However, our historical study shows that only genetic factors became effective in combination with profound changes in lifestyle, which are unique in the history of mankind.…”
Section: Resultsmentioning
confidence: 99%